A policy of demand-driven management for agricultural water use in Japan - Katsuhiro Sakurai; Ataru Nakamura; Shintaro Kobayashi; Hiroyuki Shibusawa; Hajime Tanji (European Regional Science Association (ERSA), 2014)
To this day in Japan, the water supply service for agricultural use has been formed as the supply-driven system. In fact, the farmers can use the utilization volume of agricultural water and they have to pay the price of agricultural water fee decided by water supplier side. However, diverse functions are being desired to irrigation facilities in recent years, not only conventional water supply. Those include reflection of the farmers' various needs and provision of hydrophilic environment as typical examples. Thus agricultural water supply should be regarded as irrigation services and it is needed to consider requirements for providing desired services as well as efficient water distribution. Therefore, we made case study at Aichi-Yosui (Aichi Waterworks, Japan) by following processes: investigate the demands and potential needs of farmers about irrigation services, on it, grasp the agricultural conditions quantitatively from an economic viewpoint by such as estimation of the demand function. From the interview survey, it is observed that the rice farmers of Japan have diversity in management structure and sense of values. Besides, the model analysis based on the interview survey, there is a possibility to respond each farmer having own sense of values by introducing price fluctuation policy. That means, in the scenario of price fluctuation policy satisfied two different demands concurrently, increase of profit in profit seeking farmers and decrease of the cost in balanced and cost-containment farmers. Furthermore, it is notable that agricultural production costs and profit of the entire region were also increased in addition to the immediate benefits. It is suggested as the factors of them that the most efficient planting time were selected for each farmers since this system is a measure based on market principles compared to conventional systems. In addition, this system also expected to play the role that help small-scale farmers' farming activities that may go out of business due to constraints of capital and human resources. For future works, we believe that following two points are important, (1) To clarify the current situation and issues in agricultural water services via field studies, (2) To derive concrete measures and their effectiveness via simulation analysis such as Multi Agent System.
Keywords: Q15; Q25; C61; 330; Demand-driven management; agricultural water use; irrigation facilities; water demand